Cadillo (Urena lobata) control with POST herbicides. (June 2019) - Dias, José Luiz C. S.; Duarte, Guilherme Esteves; Colombo, Wendy Linares; Sellers, Brent A.
Abstract: Cadillo is an invasive species in Florida pastures and natural areas. Despite its invasiveness, relatively few studies have evaluated cadillo management. Thus, the objective of this research was to determine effective POST herbicides for cadillo control in Florida. Greenhouse and field studies were conducted at the Range Cattle Research and Education Center near Ona, FL, in 2015 and 2016. In the greenhouse study, triclopyr-ester, aminopyralid, metsulfuron, 2, 4-D amine, aminopyralid+metsulfuron, aminocyclopyrachlor+metsulfuron, and imazapyr+aminocyclopyrachlor+metsulfuron provided ≥80% control of cadillo 28 d after treatment (DAT). Aminocyclopyrachlor at 17 and 35 g ha –1 were the only treatments with <80% control, with 70% and 75% control, respectively. Similar results were reflected in cadillo dry biomass reduction. The herbicide treatments used in the field study were triclopyr-ester, aminopyralid, 2, 4-D amine, aminocyclopyrachlor, and triclopyr+fluroxypyr. Most treatments provided excellent control in the field (≥90% control) 30 DAT, and by 60 DAT all treatments provided 100% control. Results from these studies suggest that cadillo is susceptible to many of the common POST herbicides utilized in pastures and natural areas in Florida.